A COMPARATIVE STUDY OF CHOLESTEROL CONTENTS IN EGGS OF DOMESTIC HENS AND POULTRY FARMS LAYERS - Kamran, M.A.J.; Ahmad, Qazi Rashid (Journal of Ayub Medical College Abbottabad, 1988)
Abstract: One hundred eggs of two different breeds of hens, i.e., domestic hens and layers (Starcross) were analysed for their cholesterol contents, and their results were compared. It was observed that cholesterol content of layer’s eggs was higher than domestic hen’s eggs. The cholesterol contents were found similar, on the basis of unit weight of egg-yolk in both groups. It was concluded that the cholesterol of egg-yolk was dependent on the size and weight of the egg-yolk due to various other factors.